2022
DOI: 10.1128/mbio.00571-22
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Transient Niches Shape the Microdiversity Pattern of a Bacterioplankton Population with Reduced Genomes

Abstract: Prokaryotic species, defined with operational thresholds, such as 95% of the whole-genome average nucleotide identity (ANI) or 98.7% similarity of the 16S rRNA gene sequences, commonly contain extensive fine-grained diversity in both the core genome and the accessory genome. However, the ways in which this genomic microdiversity and its associated phenotypic microdiversity are organized and structured is poorly understood, which disconnects microbial diversity and ecosystem functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…S7). This is unexpected, since in the model pelagic bacterium Ruegeria pomeroyi DSS-3, the cbb 3 -type cytochrome c oxidase is likely to be responsible for the exceptionally high affinity for oxygen and efficient oxygen consumption at nanomolar scales in this organism (Chu et al, 2022). However, cbb 3 -type cytochrome c oxidase may have other functions.…”
Section: Resultsmentioning
confidence: 99%
“…S7). This is unexpected, since in the model pelagic bacterium Ruegeria pomeroyi DSS-3, the cbb 3 -type cytochrome c oxidase is likely to be responsible for the exceptionally high affinity for oxygen and efficient oxygen consumption at nanomolar scales in this organism (Chu et al, 2022). However, cbb 3 -type cytochrome c oxidase may have other functions.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, PopCOGenT assesses population structure by inferring the extent of recombination relative to the amount of divergence between genomes and this in turn can help determine where natural genetic boundaries exist between strains [ 27 ]. PopCOGenT has been used to distinguish recent gene flow events from historical ones and to identify ancestral nodes in phylogenomic trees that lead to speciation events [ 53 ]. PopCOGenT can be used to predict the recombination pattern and population structure within bacterial species and reveal distinct populations.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to outperform earlier methods and was used to delineate population boundaries of many prokaryotic species for N e estimation 12 . We therefore used PopCOGenT to delineate populations for CHUG based on the published genomes of 39 isolates we sampled mostly from brown algae ambient seawater 25,26 as well as newly sequenced genomes of seven isolates from more diverse marine ecosystems such as regular coastal seawater and coral ambient seawater (Fig. S2).…”
Section: Genome Sizes Of the Roseobacter Group Members From Surface O...mentioning
confidence: 99%
“…Early community structure analyses based on 16S rRNA gene revealed that marine Roseobacter communities are dominated by a few uncultivated lineages 17 , whose genomes are becoming increasingly available through sequencing novel cultured members and sequencing uncultured members by single-cell genomics and metagenomic binning. Classical examples are DC5-80-3 (also named RCA or Planktomarina) [18][19][20][21] , CHAB-I-5 15,22 , ChesI-A/B (also named SAG-O19) 23 , NAC11-7 24 , and more recently CHUG 25,26 . These lineages constitute a polyphyletic group in the phylogenomic tree but form a tight pelagic Roseobacter cluster (PRC) in a dendrogram clustered from the presence and absence of gene families, reflecting their convergent evolution towards shared genome content and reduced genome sizes 22,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation